تقنية التفتيت البصري وأثرها في تشكيل بنية النص الشعري الحديث - سليمان داود, أماني; إبراهيم, حنان (My University, 2016)
تسعى هذه الدراسة إلى توضيح مصطلح التفتيت البصري، وتجتهد لتبيان التطورات البصرية التي طرأت على القصيدة العربية، والأثر الذي يتركه شكل القصيدة على المتلقي، كما تعرض لصور التفتيت البصري في نماذج من الشعر العربي الحديث؛ فمن تفتيت القصيدة إلى أجزاء، إلى تفتيت الجملة الشعرية إلى كلمات، وأخيراً تفتيت الكلمة إلى أصوات. وتظهر الدراسة العلاقة بين التفتيت البصري والأشكال البصرية الأخرى؛ كالشكل الهرمي والصليبي والمتدرج، وتتعمّق في التحليل الأسلوبي لتعبّر عن التناغم بين التفتيت والتكرار في الجملة الشعرية، وتنتهي في الحديث عن العلاقة بين المساحات البيضاء والتفتيت البصري وما تحدثه من أثر جماليّ في بناء النصّ الشعريّ. التفتيت البصري، الشعر الحديث، التحليل الأسلوبي This study seeks to clarify the term of the “visual fragmentation”, strives to clarify the visual developments in the Arab Poem, reveal the impact of the form of the poem on the receiver, and shows different forms for the visual fragmentation in the Arab Modern Poetry; starting by fragmenting the poem to parts, to breaking the whole poetry, and finally breaking the word into sounds. This study shows the relationship between visual fragmentation and other visual forms like the hierarchical, crusader and tiered forms. It also get deeper in the analytical stylistic which reflects the harmony between the fragmentation and the repetition in the poetic sentence, and it ends in talking about the relationship between the white spaces and the visual fragmentation, and what it causes of the esthetic effect in the content of the poetic text.
Keywords: التفتيت البصري، الشعر الحديث، التحليل الأسلوبي; Visual Fragmentation, the Arab Modern Poetry, Analytical Stylistic.